Pengendalian Kualitas Produksi Roti dengan Metode Statistical Process Control pada Usaha Kecil Menengah - Yunita Primasanti (Program Studi Teknik Industri Universitas Setia Budi, 2019)
The main goal of the company is basically to make a profit so that the company is able to grow in the long run. However, the demands of consumers that are constantly changing require companies to be more flexible in meeting consumer demands related to product quality. Therefore, companies must be able to maintain and improve the quality of the products produced. Quality control is important for the company so that the products produced are in accordance with the standards, both the standards set by the company as well as local and international bodies that manage quality standards. In addition, quality products should be in accordance with consumer expectations. This study aims to determine defects in bakery products using Statistical Process Control methods and provide improvement suggestions. The research object is Roti Rahmat which is a small and medium business. Data collection techniques are carried out through observation and interviews with owners and employees. The results showed that the product defects were not uniform at 52.51%, the bread was scorched at 24.55%, the contents of the bread came out at 21.15%, and others at 1.97%. Based on the causal diagram, it is known that the biggest factors that cause product defects are the production process factors and employee factors.